Atherosclerosis Pathways are Activated in Pericoronary Adipose Tissue of Patients with Coronary Artery Disease - Konwerski M; Gromadka A; Arendarczyk A; Koblowska M; Iwanicka-Nowicka R; Wilimski R; Czub P; Filipiak KJ; Hendzel P; Zielenkiewicz P; Opolski G; Gąsecka A; et al. (Dove Medical Press, 2021)
Michał Konwerski,1 Agnieszka Gromadka,2 Adam Arendarczyk,3 Marta Koblowska,2 Roksana Iwanicka-Nowicka,2 Radosław Wilimski,3 Paweł Czub,3 Krzysztof Jerzy Filipiak,1 Piotr Hendzel,3 Piotr Zielenkiewicz,2 Grzegorz Opolski,1 Aleksandra Gąsecka,1 Tomasz Mazurek1 1 1st Chair and Department of Cardiology, Medical University of Warsaw, Warsaw, Poland; 2Institute of Biochemistry and Biophysics, Polish Academy of Sciences, Warsaw, Poland; 3Department of Cardiac Surgery, Medical University of Warsaw, Warsaw, PolandCorrespondence: Tomasz Mazurek 1st Chair and Department of Cardiology, Medical University of Warsaw, Banacha Street 1a, Warsaw, 02-097, PolandTel +48 22 599 19 58Fax +48 22 599 19 57Email tmazurek@kardia.edu.plPurpose: Perivascular release of inflammatory mediators may accelerate coronary lesion formation and contribute to plaque instability. Accordingly, we compared gene expression in pericoronary adipose tissue (PCAT) in patients with advanced coronary artery disease (CAD) and non-CAD controls.Patients and Methods: PCAT samples were collected during coronary bypass grafting from CAD patients (n = 21) and controls undergoing valve replacement surgery, with CAD excluded by coronary angiography (n = 19). Gene expression was measured by GeneChip™ Human Transcriptome Array 2.0. Obtained list of 1348 transcripts (2.0%) that passed the filter criteria was further analyzed by Ingenuity Pathway Analysis software, identifying 735 unique differentially expressed genes (DEGs).Results: Among the CAD patients, 416 (30.9%) transcripts were upregulated, and 932 (69.1%) were downregulated, compared to controls. The top upregulated genes were involved in inflammation and atherosclerosis (chemokines, interleukin-6, selectin E and low-density lipoprotein cholesterol (LDL-C) receptor), whereas the downregulated genes were involved in cardiac ischaemia and remodelling, platelet function and mitochondrial function (miR-3671, miR-4524a, multimerin, biglycan, tissue factor pathway inhibitor (TFPI), glucuronidases, miR-548, collagen type I, III, IV). Among the top upstream regulators, we identified molecules that have proinflammatory and atherosclerotic features (High Mobility Group Box 2 (HMGB2), platelet-derived growth platelet (PDGF) and evolutionarily conserved signaling intermediate in Toll pathways (ESCIT)). The activated pathway related to DEGs consisted of molecules with well-established role in the pathogenesis of atherosclerosis (TFPI, plasminogen activator, plasminogen activator, urokinase receptor (PLAUR), thrombomodulin). Moreover, we showed that 22 of the altered genes form a pro-atherogenic network.Conclusion: Altered gene expression in PCAT of CAD patients, with genes upregulation and activation of pathway involved in inflammation and atherosclerosis, may be involved in CAD development and progression.Keywords: adipose tissue, inflammation, gene expression, atherosclerosis